Ultra-Wideband Filter with Dual Notch Bands Based on Ring Resonator. Issue 4 (19th May 2017) - Wang, Bin; Jing, Lin; Huang, Wen; Tan, Fei
ABSTRACT: As the ultra-wideband system is easy to be interfered by narrow-band signals, an Ultra-wideband (UWB) bandpass filter for the rejection of wireless local area network and satellite communication signals is proposed. The main resonant structure was composed of an open stubs loaded ring resonator. The cascaded open stubs increased a resonant frequency and improved the selectivity of the filter. Two notch bands were realized by coupling W-shaped short stub loaded resonators and etching complementary split rings resonators. The notch frequencies could be obtained by adjusting the size of two band-stop resonators. The UWB bandpass filter was then simulated, fabricated, and tested. Simulation results are in sound agreement with measured results. Both show that the filter has a compact size with a wide upper stopband, and dual notch bands are centered at 5.8 and 8.0 GHz, respectively, which suppressed the interference from a wireless local area network and satellite communication signals in the UWB passband.